Calidad de servicio percibido por los docentes y estudiantes de la biblioteca de la Universidad Técnica de Cotopaxi, durante el período Septiembre 2019 - Febrero 2020. - Claudio Molina, María Angélica (2020)
The University libraries have assumed an important role in education, which underlies providing a quality service to users. This project was developed with the objective of evaluating the quality of service perceived by teachers and students of the library of the Technical University of Cotopaxi in the period September 2019 - February 2020. A methodology of quantitative approach, non-experimental design and descriptive level; as an instrument, the LibQual questionnaire based on Zuñiga (2017) was used, considering (22) items with an evaluation scale from 1 to 9. Three dimensions were assessed: Affective value of the service (attention provided by staff), Library as a space (perception of the physical environment), information control (availability of physical and virtual resources). The survey was applied in person to the students and teachers of the Faculties of Administrative Sciences, Human Sciences and Sciences of Applied Engineering of the institution studied; as a result of the analysis it was identified that the three dimensions have a level of negative superiority, which shows that the quality of the library service is not higher than the expected minimum and much less than the desired one, which implies thinking about possible improvement plans.